Treatment of sickle cell anemia with 5-azacytidine results in increased fetal hemoglobin production and is associated with nonrandom hypomethylation of DNA around the gamma-delta-beta-globin gene complex. - Charache, S (1983)
Increased production of fetal hemoglobin (HbF) was observed in a patient with sickle cell anemia treated with 5-azacytidine. Each of four courses of therapy resulted in a rapid and prolonged increase in the percentage of HbF containing reticulocytes (F reticulocytes) and HbF containing erythrocytes (F cells). The percentage of HbF in peripheral blood rose from 1.8 to 8.9%. The rise in HbF production was accompanied by an increase in peripheral blood hemoglobin concentration from 8 to 12 g/dl and an increase in mean erythrocyte volume. Treatment with 5-azacytidine resulted in hypomethylation of total genomic and a Y-chromosome-specific DNA fragment isolated from both peripheral blood and bone marrow. Of 15 restriction enzyme sites around the gamma-delta-beta-globin gene complex, only 2 became hypomethylated: one 107 bases 5' to the gamma G and the other 107 bases 5' to the gamma A globin genes.